2011
DOI: 10.1097/mpa.0b013e31820bf8ac
|View full text |Cite
|
Sign up to set email alerts
|

New Prognostic Markers for Outcome of Acute Pancreatitis

Abstract: Despite some improvements over time, the reporting of important aspects of prognostic studies in acute pancreatitis remains suboptimal. The proposed REMARK-based checklist may help improve the quality and reporting of research in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Moreover, the number of followers has been constantly growing with the research on predictors of severity being arguably the most prolific area in the literature on acute pancreatitis for many years. A recent systematic review of the literature found 184 original studies that reported on 196 different predictors of severity in acute pancreatitis [3]. Strikingly, 144 of 184 (78%) studies reported a statistically significant result for at least one predictor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the number of followers has been constantly growing with the research on predictors of severity being arguably the most prolific area in the literature on acute pancreatitis for many years. A recent systematic review of the literature found 184 original studies that reported on 196 different predictors of severity in acute pancreatitis [3]. Strikingly, 144 of 184 (78%) studies reported a statistically significant result for at least one predictor.…”
mentioning
confidence: 99%
“…The systematic review mentioned above showed that there was a remarkable heterogeneity between the studies in this regard. The endpoints for the prediction of severity included multiple factor prognostic scores (APACHE II C8 and/or Ranson C3), death, local and/or systemic complications (as defined by the Atlanta symposium), Japanese criteria of severity, organ failure, pancreatic necrosis, infected pancreatic necrosis, length of hospitalisation, ICU admission, and need for surgery [3].…”
mentioning
confidence: 99%
“…With the aim of early prediction of SAP, multiorgan dysfunction syndrome and risk of death, numerous biomarkers have been iteratively studied [18]. The majority of these are inflammatory mediators reflecting the complex pathophysiological pathway of AP.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature displays a huge number of articles pointing to new potential prognostic markers for outcome of acute pancreatitis, but a recent review of these papers, despite detecting 184 studies developed with this objective, suggests that the reporting on this type of research is suboptimal, not providing enough information to allow the scientific community to come to solid conclusions about their real value [16]. As a consequence, the great majority of these new markers are not incorporated into clinical practice.…”
Section: Diagnosis Of Severe Ap and Of Nhapmentioning
confidence: 99%